The Effect of Work-Life Balance On Job Satisfaction and Productivity in The General and Financial Bureau of The Indonesian Quarantine Agency - Nurhasan, Acang; Poltak Sinambela, Lijan (International Journal of Management Science and Information Technology, 2025)
Human Resources (HR) are a critical asset for companies, playing an active role in driving, thinking, and planning to achieve organizational goals. The balance between life as a worker and as an individual (Work-Life Balance, WLB) is a fundamental aspect that companies must consider as a determinant for regulation. Employee job satisfaction significantly contributes to productivity, with satisfied employees tending to be more productive. This study aims to analyze the influence of Work-Life Balance (WLB) on employee satisfaction and productivity in the General Affairs and Finance Bureau of the Indonesian Agricultural Quarantine Agency. The research employs a descriptive quantitative method with a causal associative approach, involving 20 employees as samples. Data were collected using validated and reliable questionnaires and processed using the SmartPLS software. The analysis results show that WLB has a significant positive impact on employee satisfaction and productivity, with a p-value of < 0.05. Based on the t-statistic values, WLB has a stronger influence on productivity compared to satisfaction. Employees who can balance work demands and personal life demonstrate higher levels of satisfaction and productivity. These findings highlight the importance of managing WLB within organizational policies to enhance employee performance. The practical implications of this study suggest the need for policies such as flexible working schedules and time management training to support employee well-being and productivity.